Comparative analysis of Acinetobacter baumannii bloodstream isolates from children and adults in southern China - Xue, Fen; Xu, Hui; Gao, Nan; Li, Cheng; Fei, Fan; Zhao, Rui; Zhang, Tiantian; Liang, Shuaiyuan; Wang, Xing; Zhao, Yanfeng; Du, Xingran (Frontiers in Microbiology, 2025)
IntroductionAcinetobacter baumannii (A. baumannii) is a major pathogen responsible for hospital-acquired bloodstream infections, with multidrug-resistant (MDR) strains posing severe therapeutic challenges. Neonates are particularly vulnerable, with infections often associated with high morbidity and mortality. Thisstudy aimed to compare the genomic and phenotypic characteristics of A. baumannii isolates from children and adults.MethodsA total of 77 blood isolates of A. baumannii were collected, including 42 from children and 35 from adults. Antimicrobial susceptibility testing against 14 agents was performed. Whole-genome sequencing (WGS) was used for multilocus sequence typing (MLST), antimicrobial resistance gene and virulence gene detection, and phylogenetic analysis based on core-genome single-nucleotide polymorphisms (SNPs). Key resistance mechanisms (β-lactamase production and multidrug efflux pumps) and virulence factors (porins, lipopolysaccharides, metal acquisition systems, and secretion systems) were examined.ResultsCarbapenem resistance was significantly higher in pediatric isolates (97.6%) compared with adult isolates (65.7%). Adult isolates exhibited greater diversity in OXA-type carbapenemases. Virulence gene analysis revealed widespread distribution of porins, lipopolysaccharide synthesis genes, metal acquisition systems, and type VI secretion system components in both groups, with a higher detection rate in pediatric isolates. The majority of isolates belonged to ST2 (89.6%) and carried the blaOXA-23 gene, while ST466 and ST57 were exclusively identified in adult isolates.ConclusionThese findings demonstrate age-related differences in the resistance and virulence profiles of A. baumannii bloodstream isolates. Pediatric isolates exhibited higher carbapenem resistance and virulence gene prevalence, whereas adult isolates showed greater clonal diversity. This comparative analysis enhances understanding of A. baumannii pathogenesis across age groups and provides insights for guiding empirical therapy and strengthening infection control strategies.